SURVEY AKTIVITAS GERAK OLAHRAGA PASIEN SAKIT JIWA DI RUMAH SAKIT JIWA PROF. DR . SOEROYO MAGELANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
Research utilizes kualitatif's research approaching that meaning will reserve for word soul patient effectiveness afters gets sporting power activity. Instrument that kuesioner's sheet to patient, and kuesioner for nurse and instructor doctor. Population in observational it is soul patient that follow power activity at nuthouse, Prof. dr. Soeroyo Magelang, with sample measure of 30 patient rehabilitate. Data collecting that is utilized in this research is observation and kuesioner surveys. Analisis is data is utilize descriptive percentage. Result observationaling to point out that activity stirredding to give positive effect on recovering patient. Sporting stirred activity effectiveness gets to be seen of distinctive among patient which follow sporting power activity with patient that haven't followed sporting power activity. Conclusion of this research is effective stirred activity to help patient healing process. Writer suggests that, with acquired positive effect afters soul patient get power activity, hospital makes to program power activity as program of routine was given unto by patient psychiatry to hasten patient cure .